Urine metabolomic changes in cats with renal disease or calcium oxalate uroliths - Dennis E. Jewell; Selena K. Tavener; Regina L. Hollar; Kiran S. Panickar (PLoS ONE, 2025)
Two common problems in the urinary system of cats are renal disease (RD) and calcium oxalate (CaOx) stones. The objective of this study was to assess urine metabolomic parameters of cats with these diseases to determine metabolic abnormalities and differences between the groups. The urine metabolic profile for each cat was determined, along with their lifetime history of stone incidence and renal disease. In order to reduce the data for analysis, factor analysis/factor loading was used allowing statistical hypothesis testing and the selection of significant metabolites from 488 identified metabolites. A total of 42 cats were used (19 healthy, 12 with CaOx stones and 11 with renal disease). Urine from the cats were tested multiple times (mean = 4.6) therefore cat ID was used as a random variable. All analytes were expressed as a ratio to creatinine in order to compensate for differences in water intake. Principal components analysis was used as the method of factor extraction resulting in six factors that differed between groups. Factors 1, 2, and 5 were elevated in healthy cats and depressed in RD and CaOx cats. These factors had several analytes that are known to be elevated in the serum of cats with CaOx stones (i.e., 7-methylguanine, erythritol, pseudouridine, N1-methylinosine). Factor 5 was elevated in healthy cats containing six phenyl moieties as well as p-cresol sulfate. There were two factors which were increased in CaOx cats. Factor 12 was increased when compared to healthy cats and contained three purine nucleic acids (inosine, xanthine and hypoxanthine) as well as 3-hydroxybutyrate while factor 23 was elevated and the only factor that contained phospholipids. These results show that urine is not simply reflecting circulating concentration changes observed in cats with CaOx stones and RD but rather also gives insight into the functional kidney changes associated with these diseases.